2011
DOI: 10.1002/pip.1117
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐low concentration Na2CO3/NaHCO3 solution for texturization of crystalline silicon solar cells

Abstract: In this work, a novel diluted carbonate/bicarbonate solution was applied for texturization of monocrystalline silicon for solar cells. The content of reactants in the solution was decreased 20 times with respect to the previously optimum found by our group and 12 times with respect to the lowest values reported in the literature as optimum. The use of this low‐cost and nonhazardous solution, free of additives as isopropyl alcohol, can reduce costs in solar cell processing. Copyright © 2011 John Wiley & Sons, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…1, 2). In previous work similar surface results were shown for different Si materials after several minutes of texturization (30 min) with this ultra-low Na 2 CO 3 /NaHCO 3 solution (Montesdeoca-Santana et al, 2012). This means that the initial surface has an influence on the initiation of the texturization process.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…1, 2). In previous work similar surface results were shown for different Si materials after several minutes of texturization (30 min) with this ultra-low Na 2 CO 3 /NaHCO 3 solution (Montesdeoca-Santana et al, 2012). This means that the initial surface has an influence on the initiation of the texturization process.…”
Section: Resultssupporting
confidence: 79%
“…2b, 2c), it can also be observed that most of the bigger and well-defined pyramids are distributed in groups (marker 3), while on the rest of the surface smaller hillocks (at around 100 nm) start to form. The size of these pyramids together with the well-defined shape suggests that they are either consecutively formed and redissolved or integrated in larger pyramids during the reaction time until forming the final pyramidal morphology, in which pyramids reach a size of 2–7 μm after 30 min of texturization (Montesdeoca-Santana et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As IPA is expensive and easy polluted the environment, Thus, more and more anisotropic etching alkaline solutions has been investigated with the aim to reduce the cost of the etching process [8] . Such as TMAH [9] , Na 2 SiO 3 [10] , Na 2 CO 3 and NaHCO 3 [11] , Na 3 PO 4 [12] , and so on. In this passage.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that sodium carbonate (Na 2 CO 3 ) and sodium bicarbonate (NaHCO 3 ) can also hydrolyze in water and generate OHin order to help for forming small pyramids. Besides, among all the etching solutions, the carbonate and bicarbonate solutions could be considered to be the least harmful, dangerous and expensive [4,5,6]. So, it is reasonable to apply Na 2 CO 3 and NaHCO 3 solutions to texture monocrystalline silicon.…”
Section: Introductionmentioning
confidence: 99%